"Good Citizens" in Democratic Hard Times. Issue 1 (January 2022) - Goodman, Sara Wallace
How do citizens define their civic obligation when their country faces a democratic threat? Do citizens of a democracy think it is important to uphold liberal democratic values or to participate in governance? Do they embrace values that protect democracy, or do they just protect their political party or "side"? I examine changes to citizenship norms in the context of democratic threat using observational data from the United States, the United Kingdom, and Germany. I compare trends between 2004 and 2019, which show a weakening in the consensus of "good citizen" norms. Specifically, partisans on the left are more likely to value diversity, vigilance, and tolerance; while partisans on the right become more supportive of values like obeying the law. These differences are reduced in consensus-based political systems, but still the consequences are concerning: when the ties of citizenship norms become weaker, so too does national unity, which is integral to democratic legitimacy and stability.